Implementasi Moderasi Beragama dalam Konteks Kemajemukan Masyarakat Desa Rama Agung Bengkulu Utara: Penelitian - Suhirman; Ahmad Syarifin; Erna Nina; Ledia Soleha; Randa Wahyu Difa; Winda Nike Yuda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesia is a country rich in religious, cultural, and ethnic diversity. However, this diversity also poses challenges in maintaining social cohesion and harmony between religious communities. This study aims to describe the implementation of religious moderation values ​​in Rama Agung Village, North Bengkulu Regency, as an example of a multireligious community at the village level. A descriptive qualitative approach was used in this study with data collection techniques through in-depth interviews, participatory observation, and documentation. The results of the study indicate that the people of Rama Agung Village have internalized the values ​​of religious moderation in their daily lives through an attitude of tolerance, interfaith dialogue, and active involvement in cross-religious social activities. The role of religious leaders, village officials, and local institutions has proven significant in maintaining social harmony and strengthening the spirit of togetherness amidst differences. This study concludes that a contextual and participatory approach to religious moderation is very effective in strengthening the social cohesion of pluralistic village communities.